IMPACTOS DA PANDEMIA DE SARS-COV-2 SOBRE ASPECTOS MOTORES E COGNITIVOS NA SAÚDE DE IDOSOS: UM ESTUDO FOLLOW-UP DE 3 ANOS - THAIS CARDOSO DA SILVA (2022)
The SARS-CoV-2 virus causes the disease COVID-19. This virus is a beta coronavirus that was discovered in bronchoalveolar specimens obtained from patients with pneumonia in Wuhan City, Hubei Province, China, in December 2019. Prior to the identification of SARS-CoV-2, six coronaviruses were known to infect humans. So far, more than 630 million cases have been confirmed worldwide. Most commonly reported symptoms of COVID-19 include fever, cough, dyspnoea, myalgia, fatigue, sputum, sore throat, diarrhea, headache, anosmia, and ageusia. Social distancing makes it possible to reduce the number of cases and prevent the spread of the virus in the community. However, this social disconnect has led to a further development of mental and physical deterioration in the elderly population. The objective of this master's thesis was to analyze the impacts of the SARS-CoV-2 pandemic on motor and cognitive aspects in the health of the elderly. The sample composition of this study was based on a previous study. In this, 40 elderly people over 60 years old underwent cognitive assessments, namely the Mini-Mental State Examination (MMSE) and the Frontal Assessment Battery (BAF), and motor assessments, namely the Timed Up and Go (TUG Test) and Falls Efficacy Scale - International - BRAZIL (FES-I-BRASIL). Multiple analyzes of variance were associated with Wilk's Lambda test. Effect size (ɳ2ρ) and statistical power were reported. Significance was assumed at 5%. The results showed worsening in motor (p=0.001; ɳ2ρ=0.747; statistical power: 99.9%) and cognitive (p=0.001; ɳ2ρ=0.429; statistical power: 99.8%) decline. ) during the pandemic by the SARS-Cov-2 virus, regardless of gender, indicating a greater impact on individuals with low education. And yet, the older the individuals, regardless of gender, the worse motor scores they presented (p=0.001; ɳ2ρ=0.976, statistical power of 99.9%), therefore, the variable “age” is a risk factor for motor decline in elderly people (p=0.001 ɳ2ρ=0.779, statistical power of 99.9%). In conclusion, the research identified motor and cognitive declines in the participants during the 3-year follow-up, where, finally, the education and age variables had a great impact within the context of the lockdown, imposed on everyone during the COVID-19 pandemic. by SARS-CoV-2.